The Design and the Use of Management Control System in Developing Organizational Learning - Elsye Hatane, Saarce; Lesmanaputri, Evelin; Jesslyn Prajnawati Firman, Joan; Lisayani Wijaya, Vanny (KnE Life Sciences, 2020)
The concept of management control system and organizational learning has drawn the attention of many parties as they began to learn the importance of these tools in organizational sustainability. MCS help to ensure that problem is detected and appropriate decision are made, fundamental changes resulting from correcting the problem will promote organizational learning. The aim of this research is to examine the relationship between the design and the use of management control system in developing organizational learning. More specifically, the study focuses on four elements of organizational learning, namely knowledge acquisition, information distribution, information interpretation, and organizational memory. Two research questions are investigated in this study: i) Does the design of MCS have an impact on the elements of OL? ii) Does the use of MCS influence the elements of OL? The result suggests that there is a positive influence between the design and the use of MCS with Organizational Learning. Use of MCS has more influence on Organizational Learning when compared to the Design of MCS. This is because design will be more meaningful when used and applied. Keywords: control framework; information integration; knowledge acquisition; organizational memory; performance evaluation